Governance and role in increasing the tax outlet in Iraq (Journal of Accounting and Financial Studies ( JAFS ), 2019)
The goal of the research is to highlight the role of the governance and its characteristics in increasing the tax outcome by implementing the laws, regulations and annual controls issued annually from the general authority for taxation for the financing of the general treasury of the state, Additional development and economic capacity, As the search shares a view of the governance and its characteristics and its ideas from increasing tax output. The analytical transparent approach was used by adopting the practice of practicalities of the general authority for tax For quotations in the senior cabinet section ,the revealing of the ongoing operations was relied on the revenue for each financial year, The tools adopted in the process of analyzing the data and financial statements to adopt annual controls issued by the general authority for taxes, Which expressly retired financial proportions by the commission to put the cost of tax, The research provided a number of important conclusions: Governance is the process of formulating, implementing and implementing laws, regulations and instructions that contribute to the conduct of the daily transactions, As well as an increase in the tax outlet by applying annual controls from the general authority for tax, The research  also found a number of recommendations: The need to put scales of special and outgoing laws and the general laws are uniform for example ,the real estate tax law No.162 of 1959 exempted the bureaus of the times and valid on all layers of society by issuing legal legislation as a system to solve problems and achieve the goals from the issuance of these legislation to the various groups of society.